Analisis Sikap Mandiri Belajar Siswa dalam Pembelajaran Daring di Sekolah Dasar Swasta Wening - Rahmawati, Siti Rodiah; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Self-regulated learning at elementary school age is very important because students can have the ability to reflect on the results of the learning process. The online learning process experienced by Indonesian students today due to COVID-19 causes problems. Among them are students who experience limitations in the reach of internet information networks, less than optimal learning, students who are less enthusiastic about online schools, as well as limited student facilities. However, if students already have independent learning, students can face learning conditions in any form. So that if students can have independent learning, students will be able to reflect on their learning outcomes. The purpose of the research is to find out how independent student learning is and the second is the teacher's efforts to form student learning independence. This study uses a qualitative approach and uses a case study as a methodology. Students can be self-regulators in learning when studying online with students having internal responsibilities in doing assignments, having good learning goals, students are trained critically, having an openness to learning and students can have breadth in exploring lessons through interesting and fun learning media. Efforts are made by the teacher to establish student learning independence, namely by providing space for students to learn from wider sources, the teacher providing fun learning, using appropriate learning media, giving students space to know how to learn, and instilling a critical attitude.